2019
DOI: 10.1186/s41544-019-0035-8
|View full text |Cite
|
Sign up to set email alerts
|

miR-144/451 in hematopoiesis and beyond

Abstract: MicroRNAs (miRNAs), a class of 18-25 nucleotide (nt) non-coding RNAs, usually inhibit the expression of their target genes. They are transcribed from endogenous genes and are processed for maturation by multiple pathways. miR-144/451, a bicistronic gene locus, encodes miR-144 and miR-451, both of which are highly conserved in evolution. These two miRNAs are on the same primary RNA molecule whose transcription is controlled by multiple nuclear proteins, including GATA1, GATA4, Myc, Oct1, Pax4, FXR, AP1, SMAD3 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 109 publications
1
19
0
Order By: Relevance
“…These dynamic changes in expression of key variables (miR-451, LKB1, AMPK, OCT1) in various conditions are in good agreement with experimental observations (U252 in [14]). In particular, these theoretical predictions from our model and experimental data [14] show the important role of OCT1 (figure 3b,h) in regulation of glioma invasion and for developing therapeutic strategies [67][68][69].…”
Section: (C) Dynamics Of the Core Control Systemsupporting
confidence: 69%
“…These dynamic changes in expression of key variables (miR-451, LKB1, AMPK, OCT1) in various conditions are in good agreement with experimental observations (U252 in [14]). In particular, these theoretical predictions from our model and experimental data [14] show the important role of OCT1 (figure 3b,h) in regulation of glioma invasion and for developing therapeutic strategies [67][68][69].…”
Section: (C) Dynamics Of the Core Control Systemsupporting
confidence: 69%
“…MiR-451a (or miR-451, miRBase 22) is dicer independent and can be transcribed into a hairpin structure and then processed with the Argonaute 2 (Ago 2) protein ( Wang, Wu & Yu, 2019 ). This miRNA is stable in peripheral blood and can be found in erythrocytes, PMN, mononuclear cells and platelets ( Ghai et al, 2019 ; Masaki et al, 2007 ).…”
Section: Discussionmentioning
confidence: 99%
“…In particular, animal studies showed that the deletion of the miR-144 locus in aged mice induces the development of B-cell lymphoma and acute myeloid leukemia. The underlying mechanism is that the downregulation of miR-144 leads to the overexpression of Myc (an oncogene) in DLBCL [20]. Conversely, Montes-Moreno et al reported the upregulation of miR-144 with miR-222, miR-451, and miR-221 in the ABC-type of DLBCL [21].…”
Section: Mir-144 In Diffuse B Cell Lymphomamentioning
confidence: 99%